NodeMCU in Patient’s Data Transfer to IoT Platform - Christian, Tchapga Tchito; Daniel, Tchiotsop; Anaclet, Fomethe (British Journal of Healthcare and Medical Research, 2018)
Telemedicine is the use of advanced telecommunication tools, within the framework of clinical health, to diagnose diseases or deliver care remotely. In the field of telecommunication, many progress have been made specially with the expanding paradigm of Internet of Things. Our goal in this paper is make use of those low cost and open source tools to accurately transmit patient’s parameter to IoT platforms in order to apply a further processing techniques for remote disease diagnostic. To tackle this issue, we made use of ECG samples, sensor for temperature and humidity, connected to the NodeMCU which is one of the fast expanding and effective tools to easily establish communication with large scale data storage servers. The NodeMCU is used to push medical parameters to the ThingSpeak which is one of the most advanced IoT platform embedding MatLab. We made use of two main Application Program Interface (API): Message Queuing Telemetry Transport (MQTT) to push data to server, and the REpresentational State Transfer (REST), web services provide interoperability between computer systems on the Internet. As result of that experimentation we succefully transmited the three parameters, necessary on heart disease diagnosis. This tiny setup could be of a great help for remote medical data processing, also the IoT platform selected gives room to MatLab thereby could allow any type of further and powerful processing.